Rebels and renegades : a chronology of social and political dissent in the United States - Hamilton, Neil A., 1949- (New York : Routledge, 2002)
"In nine chronological chapters, Rebels and Renegades covers the major events and personalities in the history of radicalism and extremism in the United States. Starting with the arrival of the Pilgrims in Plymouth in 1620 and ending with the terrorist attacks of September 11, 2001, the work spans the spectrum of sociopolitical dissent, from the extreme right to the extreme left - with all shades in between."--BOOK JACKET.
Colonization and settlement -- Revolution and nation building -- Expansion and reform -- Civil War and Reconstruction -- Industrialization and the Progressive Era -- World War I and the Roaring Twenties -- The Great Depression and World War II era -- Postwar United States -- Contemporary United States.
Includes bibliographical references (p. 317-319) and index.
Keywords: Radicalism -- United States -- History; Radicals -- United States -- History; Social reformers -- United States -- History; Protest movements -- United States -- History; United States -- History